Tanggung Jawab Notaris Dalam Hal Kelalaian Merumuskan Komparisi Pada Akta Notaris - Pradana, Putu Andre Kresna; Dananjaya, Nyoman Satyayudha (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 03 (2024), 2024)
The purpose of this writing is to understand the responsibility of notaries if they are negligent in drafting the comparisi presented by the parties and to identify who is responsible for the comparisi in a deed. This journal uses a normative legal research method, specifically employing a statutory approach due to the examination of normative ambiguities. The findings indicate that in cases of notarial deed amendments containing typographical errors in the comparation or in drafting the comparation, the notary must correct and read the deed again to the parties involved. If the notary fails to correct the typographical errors, they may face civil or administrative sanctions. If the notary intentionally falsifies the comparation to benefit one of the parties, they may face criminal sanctions.